2017 MILITARY SUPPLEMENT: CURRENT CHALLENGES IN THE DEVELOPMENT OF ACELLULAR HEMOGLOBIN OXYGEN CARRIERS BY PROTEIN ENGINEERING - Benitez Cardenas, Andres S. (Shock, 2019)
This article reviews the key biochemical mechanisms that govern O(2) transport, NO scavenging, and oxidative degradation of acellular hemoglobin and how these ideas have been used to try to develop strategies to engineer safer and more effective hemoglobin-based oxygen carriers (HBOCs). Significant toxicities due to acellular hemoglobin (Hb) have been observed after the administration of HBOCs or after the lysis of red cells, and include: (a) rapid clearance and kidney damage due to dissociation into dimers, haptoglobin binding, and macrophage activation; (b) early O(2) release leading to decreased tissue perfusion in capillary beds; (c) interference with endothelial and smooth muscle signaling due to nitric oxide (NO) scavenging; (d) autooxidization of heme iron followed by production of reactive oxygen species; and (e) iron overload symptoms due to hemin loss, globin denaturation, iron accumulation, and further inflammation. Protein engineering can be used to mitigate some of these side effects but requires an in-depth mechanistic understanding of the biochemical and biophysical features of hemoglobin that regulate quaternary structure, O(2) affinity, NO dioxygenation, and resistance to oxidation, hemin loss, and unfolding.